(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Financialstatement fraud is a deliberate misstatement of material facts by themanagement in the books of accounts of a company with the aim of deceivinginvestors and creditors. This illegitimate task performed by management has asevere impact on the economy throughout the world because it significantlydampens the confidence of investors. Despite the presence of strong internalcontrol and various internal as well as external audit committees, detectingfraudulent financial reporting fraud is a difficult task when using normalaudit procedures due to the following reasons. First, there is a shortage of knowledge concerning thecharacteristics of financial statement fraud. Secondly, given its infrequency, most auditors lack the experiencenecessary to detect it. Finally,managers deliberately try to deceive auditors. For such managers, whocomprehend the limitations of any audit, standard auditing procedures may proveinsufficient. It has also been noted that the increased emphasis on systemassessment is at odds with the profession‘s position regarding fraud detection,since most material frauds originate at the top levels of the organization,where controls and systems are least prevalent and effective. These limitationssuggest that there is a need for additional analytical procedures for theeffective detection of financial statement fraud.